Extracellular vesicles and their detection with plasmonic bionsensors for the diagnosis of ovarian cancer - Reiner, Agnes (2018)
Ovarian cancer is the deadliest gynecological cancer, due to its late diagnosis resulting in unsuccessful treatment. An earlier diagnosis at a stage, when the disease is still treatable, would improve the chances of survival immensely. To achieve such an early diagnosis extracellular vesicles (EVs) have been proposed as a new class of biomarkers, but the currently used methods for their isolation and analysis lack in specificity and sensitivity. Hence this project aimed to identify new EV-based biomarkers for an improved diagnosis of ovarian cancer by usage of lipid-binding proteins for EV isolation and to develop new highly sensitive biosensors for EV detection based on surface plasmon resonance (SPR). We achieved our aim by identifying a subpopulation of EVs that carries a distinct lipid and protein composition as candidate biomarker for ovarian cancer and will validate its value for clinical application in subsequent studies. Furthermore, we developed a plasmonic biosensor platform that was capable of detecting trace amounts of EVs by making use of magnetic nanoparticles for signal enhancement. The specific detection of cancer-derived EVs with this sensing platform will be studied in future.